DEVELOPMENT OF BIOLOGY MODULE BASED ON DISCOVERY LEARNING TO INCREASE INTEREST AND LEARNING RESULTS CLASS X STUDENTS ON PLANT MATERIALS - Suryandari, Ririn (Jurnal Ilmu Pendidikan Indonesia, 2022)
This research is a research and development (Research & Development) which aims to find out how to develop a discovery learning-based biology learning module to increase the interest and learning outcomes of students class X on plant material at YPK Bethel Aimas High School, Sorong Regency.The data analysis technique used descriptive presentation to determine the feasibility of the module.Â The results of there search show that: (1) The interest of students in learning biology increased after using the biology module, before using the module is 77, 94% after using the module increased to 90.81%; (2) There is anincrease in biology learning outcomes after modules as indicated by the n-Gain value in RPP 1 of 0.52, RPP 2 of 0.63, and RPP 3 of 0.69.